2022
DOI: 10.1111/ijfs.16154
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive study on nutritional, flavour and metabolite characteristics of green prickly ash (Zanthoxylum schinifolium) at different picking stages

Abstract: The nutritional, flavour and metabolite properties of Zanthoxylum schinifolium in 10-145 days postanthesis (P10-P145) were comprehensively investigated. With increasing maturity, fruit volume and weight significantly increased, moisture content decreased. Amino acids in Z. schinifolium are mainly composed of arginine, proline, tryptophan and glutamic acid. Total amino acid content reached the highest level of 31.153 mg/g at P130. Total phenols and flavonoids contents reached the highest level at P100. The cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The volatile compounds with highest contents in the huajiao samples were linalool, germacrene D, trans-caryophyllene, linalyl acetate, sabinene, limonene and others. Other studies also reported that limonene, linalool and sabinene are the major volatile compounds in different varieties of huajiao and play an important role in the aroma characteristics [ 1 , 5 ]. In addition, a previous study reported that α-pinene and sabinene are the major volatile compounds in green huajiao [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volatile compounds with highest contents in the huajiao samples were linalool, germacrene D, trans-caryophyllene, linalyl acetate, sabinene, limonene and others. Other studies also reported that limonene, linalool and sabinene are the major volatile compounds in different varieties of huajiao and play an important role in the aroma characteristics [ 1 , 5 ]. In addition, a previous study reported that α-pinene and sabinene are the major volatile compounds in green huajiao [ 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…Huajiao ( Zanthoxylum bungeanum Maxim), the fruit of plants of the genus Zanthoxylum , a deciduous small tree or shrub, has been cultivated for more than 2000 years and is an endemic and resource-rich spice for traditional Chinese medicine in China [ 1 , 2 , 3 , 4 ]. According to the color of its pericarp, it can be divided into two main categories, red huajiao and green huajiao [ 5 ]. Green huajiao ( Zanthoxylum schinifolium Sieb.…”
Section: Introductionmentioning
confidence: 99%